Effect of selective β-adrenoceptor blockade and surgical resection of the celiac-superior mesenteric ganglion complex on delayed liquid gastric emptying induced by dipyrone, 4-aminoantipyrine, and antipyrine in rats - Vinagre,A.M. (2016)
There is evidence for participation of peripheral β-adrenoceptors in delayed liquid gastric emptying (GE) induced in rats by dipyrone (Dp), 4-aminoantipyrine (AA), and antipyrine (At). The present study aimed to determine whether β-adrenoceptors are involved in delayed GE induced by phenylpyrazole derivatives and the role of the prevertebral sympathetic nervous system in this condition. Male Wistar rats weighing 220-280 g were used in the study. In the first experiment rats were intravenously pretreated with vehicle (V), atenolol 30 mg/kg (ATE, β1-adrenergic antagonist), or butoxamine 25 mg/kg (BUT, β2-adrenergic antagonist). In the second experiment, rats were pretreated with V or SR59230A 2 mg/kg (SRA, β3-adrenergic antagonist). In the third experiment, rats were subjected to surgical resection of the celiac-superior mesenteric ganglion complex or to sham surgery. The groups were intravenously treated with saline (S), 240 µmol/kg Dp, AA, or At, 15 min after pretreatment with the antagonists or V and nine days after surgery. GE was determined 10 min later by measuring the percentage of gastric retention (%GR) of saline labeled with phenol red 10 min after gavage. The %GR (means±SE, n=6) values indicated that BUT abolished the effect of Dp (BUT+Dp vs V+Dp: 35.0%±5.1% vs 56.4%±2.7%) and At (BUT+At vs V+At: 33.5%±4.7% vs 52.9%±2.6%) on GE, and significantly reduced (P<0.05) the effect of AA (BUT+AA vs V+AA: 48.0%±5.0% vs 65.2%±3.8%). ATE, SRA, and sympathectomy did not modify the effects of treatments. These results suggest that β2-adrenoceptor activation occurred in delayed liquid gastric emptying induced by the phenylpyrazole derivatives dipyrone, 4-aminoantipyrine, and antipyrine. Additionally, the released neurotransmitter did not originate in the celiac-superior mesenteric ganglion complex.